Comparative analysis of Grammar Checkers of various Asian Languages - Verma, Vikas; Sharma, S.K (International Journal of Computer Sciences and Engineering, 2025)
The processing of natural languages using Computational Linguistics is an important domain of NLP(Natural Language processing). Many sentences are written in a natural language which may be defined as units, explicitly "linguistic units" which are meaningful and involve one or more words linked together in accordance with a set of predefined rules called ‘Grammar’. Grammar checking is the task of detection and correction of grammatical errors in the text. Though a lot of work is done particularly for English language yet scant work is done for various Asian languages. This paper explores the contribution made by various researchers in this sphere. This paper critically analyses advancements made in relevance to global context. This facilitates better understandability, comparison and evaluation of previous research